Síntese e caracterização de membranas de triacetato de celulose a partir do aproveitamento do bagaço de cana-de-açúcar para a liberação controlada de drogas - Ribeiro, Sabrina Dias (2012)
This work presents a study of the use of sugarcane bagasse as an alternative source of cellulose, for obtaining cellulose triacetate (CTA) and consequently production of membranes for use in controlled release system (CRS) of the drugs naproxen (water insoluble) and doxycycline (water soluble). The sugarcane bagasse was delignified from three successive reflux of a mixture 80/20 (v/v) nitric acid concentrated and ethanol, subsequently treated in NaOH solution. From the analysis of Klason Lignin, noted that in delignified bagasse (DB) there was a reduction in lignin content of 98% compared with gross bagasse. CTA produced presented degree of substitution (DS) 2.80 ± 0.09, what classifies as cellulose triacetate (CTA). The formulations used, CTA/dichloromethane/drug and CTA/dichloromethane/water/drug led to the production of symmetric and asymmetric I membranes, respectively. The formulation with the system solvent dioxane/acetone resulted in asymmetric II membranes with pores in thickness and dense surface, morphologies observed from the analysis of scanning electron microscopy (SEM). The results of the thermal analysis showed that there are interactions between drugs and the CTA. The polymeric matrices showed Swelling index (Si) approximately 12%, a result that will influence on the release kinetics of drugs. The content of naproxen released was 8, 50 and 25% from symmetric, asymmetric I and asymmetric II membranes, respectively. Doxycycline presented release content 14% in experiments with symmetric membranes and 80% with asymmetric I membranes. The study of CRS of drugs showed that membrane morphology has great influence on drugs desorption and the release occurs predominantly by diffusion.